Negosiasi Adat dan Syariat: Tradisi Penne Anreang pada Pernikahan Bugis serta Relevansinya terhadap Hukum Keluarga Islam - Manggabarani, Andi Ishaka; Soumena, Yasin; Rahmawati, Rahmawati; Nur Tajuddin, Fatjri; Azizah, Luthfiah (IAIN Parepare, 2024)
This study examines the penne anreang tradition in Bugis wedding ceremonies in Suppa District, Pinrang Regency, focusing on its philosophical significance and compatibility with Islamic law. The research aims to describe the implementation of penne anreang, analyze its symbolic and philosophical meanings, and assess its position within the frameworks of ‘urf shahih and mashlahah mursalah. A qualitative methodology was employed through participant observation and in-depth interviews with cultural leaders, religious figures, and practitioners, followed by thematic analysis to identify embedded social and religious values. The findings reveal that penne anreang functions as a symbol of marital responsibility, reinforcing values such as unity, humility, and mutual support. It qualifies as ‘urf shahih because it aligns with Islamic legal principles while simultaneously strengthening social cohesion. However, younger generations increasingly perceive the practice as mere formality, threatening the loss of its philosophical essence. This study contributes to broader debates on Islamic law and legal pluralism by demonstrating how local customs can be integrated with Sharia without eroding cultural identity. The findings underscore the importance of intergenerational education to sustain the philosophical values of local traditions in the face of modernization.